Assessing Students During Online Learning: A Case Study on a Linguistic Subject Teacher’s Experience - Aji, Aulia Adilla; Basthomi, Yazid (Language Circle: Journal of Language and Literature, 2022)
Online learning has caused major shifts, including the assessment process inside the English Language Teaching classroom. Through a series of in-depth interviews and thorough observations, this study explored a Linguistic Subject teacher’s experience in implementing an online assessment using a Learning Media System (LMS) application called Microsoft Teams. The use of the Microsoft Teams Application helped to improve efficiency in uploading the files of students’ assignments, correcting and giving feedback to their works. However, based on the interviews, some obstacles were found during the teaching, learning and evaluation process. These include network problems, shorter time of classes and massive collusion among students make the students’ performance in doing their assignments do not always reflect their understanding and ability. While network problems and shorter face to face interaction often hinder the teaching and learning process as well as the assessment of students’ active participation, the use of blended learning in the school required teachers to be more creative and assertive in the assessment process.